(untitled) (Global Scientific Review, 2023)
This article focuses on the issues of arbitrability of disputes on the territory of the Republic of Uzbekistan. The categories of disputes of contractual and noncontractual nature are considered in detail through the prism of their arbitrability in accordance with the current legislation of Uzbekistan with the introduction of precise regulatory legal acts. The article targets both law school students and practicing lawyers in the field of arbitration and state proceedings.